Análise do quantitativo de pessoal da educação superior federal durante o regime fiscal do teto de gastos (2016 a 2023) - Eliseu, Renan Amaral (2024)
This research aimed to better understand the variation in the number of personnel in Federal Higher Education during the period of the fiscal rule established by Constitutional Amendment 95/2016, commonly known as the "Spending Cap." This was a significant fiscal austerity measure by the Brazilian state that set specific criteria and strict limits on discretionary spending by the federal government within the scope of the Union's Fiscal and Social Security Budgets, which may have directly affected essential services in areas such as Education. The analysis of the collected data was conducted with a qualitative focus through comprehensive bibliographic and documentary research. To support the discussion of the topic, brief yet insightful discussions were held on the subjects of Fiscal Austerity, Development, and the State. The Statistical Personnel Panel of the Ministry of Planning was used as a primary source for collecting detailed data related to personnel numbers. A broad 20-year period was adopted as the time frame to better observe trends and variations over time, comparing them with what was recorded during the period of the fiscal measure of the Spending Cap (2016 to 2023). In this context, specific information was gathered and meticulously analyzed from the categories of Technical-Administrative in Education and Professor of Higher Education, which are the most representative within Federal Higher Education. Additionally, to better understand the broader context in which these servers are located, data were also collected regarding the number of active civil personnel in the Federal Executive Branch under the Union's Single Legal Regime. Similarly, information on enrollments in the federal public higher education network was gathered from the Higher Education Census of the National Institute of Educational Studies and Research Anísio Teixeira. Finally, it was found that, during the period coinciding with the fiscal adjustment, there was a notable 4.6% reduction in the number of Technical-Administrative in Education, while there was a 4.6% increase for Professors of Higher Education. In the same period, the Brazilian population increased by approximately 5.4%, and the variation in the number of enrollments in Federal Higher Education Institutions was proportionally higher, at 7.6%. There was also a slight but relevant increase of 2.34% in the number of enrollments in federal universities. Considering the significant numerical representation of Technical- Administrative in Education in Federal Higher Education Institutions, it is concluded that, without changes in hiring trends and career valuation, the expansion of access to Federal Higher Education may be severely compromised. Although an increase in the number of Professors of Higher Education was observed during the analyzed period, it is necessary to carefully investigate the potential impacts that the reduction of Technical-Administrative in Education may have on that category and the complex factors that contribute to the precariousness of work in the career.